Probing depth is an independent risk factor for HbA1c levels in diabetic patients under physical training: a cross-sectional pilot-study - Wernicke, Katharina; Zeissler, Sven; Mooren, Frank C.; Frech, Torsten; Hellmann, Stephanie; Stiesch, Meike; Grischke, Jasmin; Linnenweber, Silvia; Schmidt, Bernhard; Menne, Jan; Melk, Anette; Bauer, Pascal; et al. (BMC oral health, 2018)
Background This cross-sectional study investigates the potential association between active periodontal disease and high HbA1c levels in type-2-diabetes mellitus subjects under physical training. Methods Women and men with a diagnosis of non-insulin-dependent diabetes mellitus and ongoing physical and an ongoing exercise program were included. Periodontal conditions were assessed according to the CDC-AAP case definitions. Venous blood samples were collected for the quantitative analysis of HbA1c. Associations between the variables were examined with univariate and multivariate regression models. Results Forty-four subjects with a mean age of 63.4 ± 7.0 years were examined. Twenty-nine subjects had no periodontitis, 11 had a moderate and 4 had a severe form of periodontal disease. High fasting serum glucose ( p < 0.0001), high BMI scores ( p = 0.001), low diastolic blood pressure ( p = 0.030) and high probing depth ( p = 0.036) were significantly associated with high HbA1c levels. Conclusions Within the limitations of this study HbA1c levels are positively associated with high probing pocket depth in patients with non-insulin-dependent diabetes mellitus under physical exercise training. Control and management of active periodontal diseases in non-insulin-dependent patients with diabetes mellitus is reasonable in order to maximize therapeutic outcome of lifestyle interventions.